DNAble® Molecular Detection Kit for Salmonella. (27th November 2019) - Dutta, Vikrant; Guerrette, Tom; Davis, Alan H; Crowley, Erin; Flannery, Jonathan; Bastin, Benjamin; Bird, Patrick; Benzinger, M Joseph; Agin, James; Goins, David
Abstract: The DNAble Salmonella detection assay utilizes single overnight culture enrichment, user-friendly sample preparation, and isothermal DNA amplification for Salmonella detection. This report describes studies performed in support of AOAC Research Institute Performance Tested Method SM certification of the DNAble assay. Selectivity (inclusivity and exclusivity) studies were performed in the sponsor's laboratory. DNAble detected 119 out of 120 Salmonella isolates, representing 100 Salmonella serovars, in the inclusivity study while none of the 35 diverse non -Salmonella strains (32 species) tested was detected in the exclusivity study. Consistency (lot-to-lot and stability), instrument variation, and robustness studies were also conducted by the sponsor. Statistically equivalent assay performance was observed in these studies demonstrating robust assay manufacture and performance despite variation of multiple parameters in these challenges. Matrix studies, performed in an independent laboratory, evaluated DNAble assay performance in dry pet food, on stainless steel surfaces, and poultry environmental drag swab samples. Two sample sizes (25 and 375 g) and two culture volumes (9:1 and 3:1, v/w) were evaluated in separate matrix studies for dry pet food to provide multiple certified testing options for assay users. DNAble assay performance for dry pet food and stainless steel was compared to the procedures described in the U.S. Food and Drug Administration (FDA) Bacteriological Analytical Manual, Chapter 5, Salmonella . Assay performance for drag swabs was compared to protocols dictated in the FDA Environmental Sampling and Detection of Salmonella in Poultry Houses guidelines. Matrix study results demonstrated statistically equivalent DNAble assay performance compared to these reference methods, ensuring that the DNAble assay provides results comparable to those of the reference methods.